2023
DOI: 10.3390/su15031847
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being of Historical Neighborhood Residents in Beijing: The Impact on the Residential Environment

Abstract: The protection of historical neighborhood blocks is the key to maintaining Beijing’s historical and cultural significance. These districts in Beijing carry the history and culture of the city, however, their increasingly crowded environments and lack of infrastructure significantly affects the quality of life for residents. A regression analysis model is constructed in this paper based on data from a 2019 urban physical examination questionnaire deployed in Beijing. Beijing’s historical districts are taken as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lovejoy et al (2010) [40] identified a connection between neighborhood satisfaction and factors related to the service environment, including location and accessibility to various amenities. Similarly, research by Yazhuo Jiang et al [42] highlights the role of service facilities such as parking, childcare, and daily shopping provisions in shaping residential satisfaction.…”
Section: Influential Attributes In Posting-industrial Neighborhoods A...mentioning
confidence: 97%
“…Lovejoy et al (2010) [40] identified a connection between neighborhood satisfaction and factors related to the service environment, including location and accessibility to various amenities. Similarly, research by Yazhuo Jiang et al [42] highlights the role of service facilities such as parking, childcare, and daily shopping provisions in shaping residential satisfaction.…”
Section: Influential Attributes In Posting-industrial Neighborhoods A...mentioning
confidence: 97%
“…Some scholars use GIS to assess the landscape sensitivity of historical districts, as seen in the works of Fang et al [42] and Yang and Shen [43]. As the concept of a people-centred approach gradually takes hold,scholars are no longer confined to studying historical districts from an objective perspective.The third type explores the relationship between people and historic districts from a human perspective.Some scholars consider the relationship between historical districts and their residents from the perspective of residents' roles [44,45]. Others explore heritage tourism in historical districts from the perspective of visitors [46,47].…”
Section: Study On the Preservation And Utilization Of Historic Districtsmentioning
confidence: 99%
“…After literature research, we are aware of the studies conducted by researchers on residential satisfaction from different perspectives (Table 1). Jiang et al [23] analyzed the influencing factors of residential satisfaction and their effects on subjective well-being in a historic district. Mridha [24] explored the significant correlation of residential satisfaction with age, gender, and marital status, and Aksel et al [25] noted that place attachment is positively related to residence satisfaction.…”
Section: Residential Satisfactionmentioning
confidence: 99%